The charitable activities as the basis of the social work - Сичова, В. В.; Полонець, Т. С. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2020)
The growth in the number of the country’s charitable organizations, transformation of one-time humanitarian actions (charity) into regular social work with veterans of the Russian-Ukrainian war (since 2014) and internally displaced persons from Donbas, the Autonomous Republic of Crimea have put on the agenda a study of the relationship between charitable activities and social work. The expansion of social work aimed at the elderly, which is often performed by the employees of territorial centers of social services beyond their job descriptions, also determines the relevance of this topic.The task of the study was to substantiate the place of charity in social work, based on the analysis of the activities of the Ukrainian charitable foundations, and employees of six territorial centers of social services in Kharkiv region.It was found that the All-Ukrainian social program “Home Care” of the International Charitable Foundation “Caritas Ukraine” represents social work with people who are not clients of territorial centers of social services. The Regional Landscape Park “Feldman Ecopark” (the flagship project of the International Charitable Foundation “Aleksandr Feldman Foundation”) is often used for social work, particularly with the elderly. It has been substantiated that the charitable activity of these foundations creates conditions for conducting systematic daily social work, in particular, with the elderly.The results of the expert survey of 16 social workers and 21 social workers of the territorial centers of social services of Bohodukhiv, Izium, Krasnokutsk, Lozova, Chuguiv, and Kharkiv districts of Kharkiv region show that charity occupies the leading place in their activities, creating conditions for social work. Charitable activities such as volunteering, social services of public/charitable organizations for the elderly are rightly regarded by experts as social work. The types of social work with the elderly in rural areas, carried out in spare time, such as helping in vegetable gardens, nature rides (in particular, to Feldman Ecopark), group communication on topical issues are referred by the experts to charitable activities.There is a partial overlapping of the subject areas of social work and charity, as well as a common goal – to help. Social workers and officials of the territorial centers of social services in Kharkiv region, performing daily social work with the elderly, often carry out charitable activities, too.It has been proved that charity helps to increase the efficiency of social work, solving many social problems of the territorial community.